Regulation of Neuronal Glutathione Synthesis - Koji Aoyama; Masahiko Watabe; Toshio Nakaki (Elsevier, 2008)
The brain is among the major organs generating large amounts of reactive oxygen species and is especially susceptible to oxidative stress. Glutathione (GSH) plays critical roles as an antioxidant, enzyme cofactor, cysteine storage form, the major redox buffer, and a neuromodulator in the central nervous system. GSH deficiency has been implicated in neurodegenerative diseases. GSH is a tripeptide comprised of glutamate, cysteine, and glycine. Cysteine is the rate-limiting substrate for GSH synthesis within neurons. Most neuronal cysteine uptake is mediated by sodium-dependent excitatory amino acid transporter (EAAT) systems, known as excitatory amino acid carrier 1 (EAAC1). Previous studies demonstrated EAAT is vulnerable to oxidative stress, leading to impaired function. A recent study found EAAC1-deficient mice to have decreased brain GSH levels and increased susceptibility to oxidative stress. The function of EAAC1 is also regulated by glutamate transporter associated protein 3-18. This review focuses on the mechanisms underlying GSH synthesis, especially those related to neuronal cysteine transport via EAAC1, as well as on the importance of GSH functions against oxidative stress. Keywords:: glutathione, cysteine, excitatory amino acid carrier, 1 (EAAC1), glutamate transporter associated protein (GTRAP) 3-18, oxidative stress